Hepatic and Gastrointestinal Complications during COVID-19: A Meta-Analysis of Meta-Analyses - Jaseela Majeed; Sapna Yadav; Rekha Garg Garg; Danish Kamal; Ramsha Iqbal; Palka Mittal; Abhishek Dadhich; Puneeta Ajmera (Journal of the Dow University of Health Sciences, 2023)
Objective: This meta-analysis is aimed to quantify the findings of different meta-analyses performed on the association of hepatic and gastrointestinal complications and COVID-19 severity. Methods: Four databases i.e., PubMed, Google Scholar, Cochrane, and Web of science were used for the systematic search of the literature from January 2020 till July 2021. “Quality of Reporting of Meta-analyses (QUOROM) checklist was used to examine the comprehensiveness of reporting in the meta-analysis. Sixteen Systematic review and meta-analysis studies met inclusion criteria. Results: Pooled results indicated that diarrhea was a significant symptom in COVID-19 patients (OR=2.70, 95% CI 1.16-6.29, p=0.02) along with abdominal pain (OR=3.87, 95% CI 2.86-5.23, p<0.01), nausea (OR=2.81, 95% CI 1.13-6.97, p= 0.03), and vomiting (OR= 2.91, 95% CI 1.31-6.49, p= 0.009). Pooled results also indicated a rise in ALT level (OR= 3.81, 95% CI 1.71-8.45 p=0.0010) and bilirubin level (OR= 2.89, 95% CI 1.38-6.04, p=0.0005) in COVID-19 patients. A significant association of AST with COVID-19 (OR=5.81, 95% CI 2.82-12, p<0.01) was also present. Conclusion: SARS-COV-2 can cause damage to the liver cells which may lead to an elevated level of inflammatory markers and liver enzymes (ALT/AST).